Perception of medical college students towards online learning amid COVID-19 pandemic - Patil, Jyoti M.; Dixit, Umesh R. (International Journal Of Community Medicine And Public Health, 2023)
Background: The nationwide lockdown restrictions to control the spread of COVID-19 impacted all aspects of life and inevitably, medical education was also affected. All medical colleges were forced to suspend face-to-face teaching and adopt online teaching. This study aimed to assess the perception of undergraduate medical students towards online learning which was adopted amid COVID-19 pandemic and to determine the perceived barriers and merits of online learning. Methods: This cross-sectional study was conducted among undergraduate medical students of a private medical college in Dharwad. A pre-designed and pre-tested proforma (Google Form) was shared via WhatsApp group. Data obtained was analysed using SPSS version 20.0. Results: A total of 201 undergraduate medical students participated in the study of which 51.2% were male and 48.8% female. The mean age of study participants was 20.3±1.02 years. Majority (71.1%) of the students used mobile phones to attend online classes. Majority (82.7%) of the students preferred face-to-face teaching over online teaching. 79% students perceived that online teaching was not as effective as face-to-face teaching and 86.1% were not able to learn clinical skills through online learning. Poor internet connectivity, family distraction, inability to meet friends, lack of co-curricular activities, and difficulty in concentration were barriers to online learning. Conclusions: The present study found that, students had negative perception towards online learning. It is important that medical schools and educators know the barriers and advantages of online learning, and come out with solutions to make online learning more acceptable to the students.